Dynamic programming in optimization of load selection for machine tools in manufacturing environment - Gojković, Donka; Banjac, Dragan (Journal of Production Engineering, 1994)
The required levels of manufacturing and economic effects in manufacturing systems in modern metalworking industry can be achieved by design and optimization of technological and manufacturing processes and their rational implementation in manufacturing environment. In order to improve productivity and cost effectiveness, special importance is attached to the implementation of appropriate systems and methods for techno-economical optimization among which is the dynamic programming method, Based on the results of a wider research in optimization of technological solutions, this paper reviews a part of results pertaining to the implementation of dynamic programming of optimal production control restricted to optimal utilization of available equipment.